Metaverse-Based Cyber Harassment and Virtual Reality: A Critical Review of The Current Legal Framework and Recommendations on Normative Needs - Lala, Andi (Politeknik Siber Cerdika Internasional, 2025)
This study explores the phenomenon of cyber harassment in the metaverse and virtual reality as a growing form of digital violence that challenges the adequacy of existing legal frameworks. Using a qualitative approach with desk research and normative-analytical methods, this study examines the conceptual, juridical, and normative dimensions of virtual harassment and its implications for national and international law. The study's findings reveal that the immersive nature of virtual interactions generates new forms of harassment, such as verbal abuse, avatar manipulation, and non-consensual virtual contact, which have significant psychological impacts on victims. The study identifies a legal gap in Indonesian law, as existing regulations such as the ITE Law do not recognize virtual identities (avatars) or address immersive digital violations. A comparative analysis shows that countries such as South Korea, Japan, and the European Union have begun to develop preventive and ethical regulatory frameworks for metaverse governance. The study concludes that Indonesia urgently needs normative reforms to recognize the existence of virtual persons, enforce platform accountability, and integrate digital ethics into its legal structure to ensure user protection in virtual spaces.